Laboratory Predictors of Esophageal Varices in Children with Chronic Liver Disease (Faridpur Medical College Journal, 2021)
Variceal bleeding results as a consequence of portal hypertension and it is a leading cause of morbidity and mortality of children with chronic liver disease (CLD). Upper gastrointestinal endoscopy is the only confirmatory tool for detecting esophageal varices but due to its invasive nature, high cost and lack of available facilities for pediatric endoscopy, alternative laboratory predictors are essential. In this study, we aimed at identifying laboratory predictors that may predict the presence of esophageal varices in children with CLD. This cross-sectional study was done at the department of Pediatric Gastroenterology and Nutrition, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from July 2008 to June 2010. Fifty consecutive children with CLD, aged 3-15 years of both sexes, who had no history of active/recent variceal bleeding, taking beta blockers or surgery for esophageal varices were included in the study. All patients underwent history and physical examination. Venous blood of the patients was taken for laboratory analysis of serum bilirubin, serum alanine aminotransferase, serum albumin, platelet count and International Normalization Ratio (INR). Later, upper gastrointestinal endoscopy of the patients were done. Based on endoscopic findings children were divided into two groups. Group-I: CLD with esophageal varices included 29 children and Group-II: CLD without esophageal varices included 21 children. A univariate analysis was initially done on laboratory variables followed by a logistic regression analysis to identify the independent variables associated with presence of esophageal varices. Then performance of these independent variables were analyzed using upper gastrointestinal endoscopy as the gold standard test. Out of 50 patients 30 were male. Male-female ratio was 1.5:1. Fifty eight percent (29 out of 50) had esophageal varices. Amongst all the laboratory variables, thrombocytopenia (platelet count